2019
DOI: 10.1097/md.0000000000017661
|View full text |Cite
|
Sign up to set email alerts
|

Primary extranodal natural killer/T-cell nasal-type lymphoma of spine

Abstract: Rationale: Primary Extranodal Natural Killer/T-Cell Nasal-Type Lymphoma (ENKTCL) of spine is rarely reported. This case study presents a rare case of ENKTCL originating from the sixth thoracic vertebra.Patient concerns: Here, we present a case of 49-year-old Asian male with chest and back pain. Physical examination revealed the myodynamia of both lower limbs decreased from IV degree to 0 degree, reflexes of both lower limbs and a large area of cutaneous sensation below xiphoid process disappeared in 3 days.Dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…This result is consistent with the studies of Wang et al, which all confirmed that 32 P application combined with thiomolol maleate significantly improved the cure rate and therapeutic effect in children with cutaneous hemangioma. In other words, as a kind of external irradiation, a certain dose of radionuclide is close to the lesion site, and the biological effect of ionizing radiation on the lesion site through radiation can reduce the rate of cell division, prolong the interval of nuclear division and occlusion of microvessels, so as to achieve the therapeutic purpose (22,23) .…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with the studies of Wang et al, which all confirmed that 32 P application combined with thiomolol maleate significantly improved the cure rate and therapeutic effect in children with cutaneous hemangioma. In other words, as a kind of external irradiation, a certain dose of radionuclide is close to the lesion site, and the biological effect of ionizing radiation on the lesion site through radiation can reduce the rate of cell division, prolong the interval of nuclear division and occlusion of microvessels, so as to achieve the therapeutic purpose (22,23) .…”
Section: Discussionmentioning
confidence: 99%
“…In search of the literature, we identified three cases of PSENKTL 7–9 . Table 1 summarized the clinicopathological features of the three cases and ours.…”
Section: Discussionmentioning
confidence: 99%
“…In search of the literature, we identified three cases of PSENKTL. [7][8][9] Table 1 summarized the clinicopathological features of the three cases and ours. The median age at presentations was 49 years old with a male predominance (M:F = 3:1).…”
Section: Case Reportmentioning
confidence: 99%
See 2 more Smart Citations